Understanding the mechanisms of efficacy of fecal microbiota transplant in treating recurrent Clostridioides difficile infection and beyond: the contribution of gut microbial-derived metabolites. Issue 1 (9th November 2020) - Martinez-Gili, Laura; McDonald, Julie a K; Liu, Zhigang; Kao, Dina; Allegretti, Jessica R; Monaghan, Tanya M; Barker, Grace F; Miguéns Blanco, Jesús; Williams, Horace R T; Holmes, Elaine; Thursz, Mark R; Marchesi, Julian R; et al.
ABSTRACT: Fecal microbiota transplant (FMT) is a highly-effective therapy for recurrent Clostridioides difficile infection (rCDI), and shows promise for certain non-CDI indications. However, at present, its mechanisms of efficacy have remained poorly understood. Recent studies by our laboratory have noted the particular key importance of restoration of gut microbe-metabolite interactions in the ability of FMT to treat rCDI, including the impact of FMT upon short chain fatty acid (SCFAs) and bile acid metabolism. This includes a significant impact of these metabolites upon the life cycle of C. difficile directly, along with potential postulated additional benefits, including effects upon host immune response. In this Addendum, we first present an overview of these recent advancements in this field, and then describe additional novel data from our laboratory on the impact of FMT for rCDI upon several gut microbial-derived metabolites which had not previously been implicated as being of relevance.